A new Obliquogobius Koumans, 1941 (Teleostei: Gobiidae) from Kumejima, Ryukyu Islands, Japan - Chen, I-Shiung; Jaafar, Zeehan; Shao, Kwang-Tsao (Zootaxa, 2012)
A new species of Obliquogobius was collected from the deep waters off Kumejima, Ryukyu Islands, Japan. The new species may be distinguished from its congeners by the following combination of characters: second dorsal fin rays I/9; anal fin rays I/10; pectoral fin rays 21; longitudinal scale rows 22; transverse scale rows 7; gill opening wide, extending to vertical of rear margin of pupil; colouration in preservative: ground colour beige; no markings on body except for inverted-triangular grayish-black mark on head, the broad end originating below eye and the apex terminating at the posterior extent of the lower jaw, and dorsal third of caudal fin dusky with random small black spots on fin membrane and life colouration: vertical yellow band under eye; one wide longitudinal yellow band originating on the posterior end of the operculum coursing along mid-flank, terminating at posterior end of caudal fin, band increasingly wider, such that posterior half of body completely yellow and band tapering in width to cover only lower two-thirds of caudal fin region.